2002
DOI: 10.1093/annonc/mdf256
|View full text |Cite
|
Sign up to set email alerts
|

Early restaging positron emission tomography with 18F-fluorodeoxyglucose predicts outcome in patients with aggressive non-Hodgkin’s lymphoma

Abstract: Early restaging [(18)F]FDG-PET may be used to tailor induction chemotherapy in patients with aggressive NHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
177
2
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(195 citation statements)
references
References 22 publications
10
177
2
6
Order By: Relevance
“…[5][6][7][8][9][10][11] The superiority of PET over computed tomography in identifying active disease after therapy completion has recently led to the revision of response criteria. 32 Several studies have shown that after 1-3 cycles of chemotherapy for aggressive NHL, 3,[5][6][7][8][9][10][11]34 early metabolic changes as documented by early or interim PET scan may be highly predictive of final treatment response and progression-free survival. However, the real benefit of interim PET in aggressive NHL has been questioned recently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10][11] The superiority of PET over computed tomography in identifying active disease after therapy completion has recently led to the revision of response criteria. 32 Several studies have shown that after 1-3 cycles of chemotherapy for aggressive NHL, 3,[5][6][7][8][9][10][11]34 early metabolic changes as documented by early or interim PET scan may be highly predictive of final treatment response and progression-free survival. However, the real benefit of interim PET in aggressive NHL has been questioned recently.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In particular, several studies that have evaluated the role of PET as a prognostic tool during chemotherapy have reported its ability to predict outcomes in aggressive NHL. [5][6][7][8][9][10][11] In force of the pivotal role played by PET in staging, restaging, and response evaluation, the International Workshop Criteria for malignant lymphoma 12 have been revised to incorporate the PET data in NHL outcome assessment, but only at the end of therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…48 Initial retrospective studies in DLBCL suggested a dramatic difference in outcome for patients with positive and negative findings on interim PET. 49,50 Subsequent prospective studies have not found such a dramatic difference, and some patients with a positive interim PET result may still have a favorable outcome. 51 One approach under investigation for patients with negative early interim PET findings, particularly those with Hodgkin lymphoma, is to employ chemotherapy-reduction strategies.…”
Section: Interim Scans (To Direct Treatment)mentioning
confidence: 99%
“…An interesting development in the role of PET for HD and aggressive NHL patients will be to verify and to confirm the preliminary data reported by Spaepen et al (2002) concerning the possible role of an early PET scan performed after a few courses of induction chemotherapy for identification and stratification of responder and nonresponder patients. This could lead to inclusion of PET in a specific mixed prognostic score including biological, clinical and imaging parameters.…”
Section: Discussionmentioning
confidence: 79%